Pengembangan Wawasan Islam Kebangsaan Mahasiswa Melalui Konseling Sebaya di Masjid Kampus - Lukman Fauroni; M. Rusydi; Maftukhatusolikhah Maftukhatusolikhah; Nur Mukhlis Zakaria (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2019)
Radicalism can pervade in all religions, the only difference lies in the model of expression and intensity. Symptoms in the realm of student religious life are beginning to be revealed. In the context of Islam, the participation of university mosques will have a significant impact in solving the problems of religious and national relations with the creation of a peaceful academic culture. Through literature studies, mosques can become facilitators for student congregations to be directly involved in overcoming peer problems, especially in promoting an anti-violence national Islam.